EKSPERIMENTASI MODEL PEMBELAJARAN GI DENGAN PENDEKATAN QL PADA PECAHAN TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI GAYA BELAJAR DAN KREATIVITAS SISWA - Binti Anisaul Khasanah; Budiyono Budiyono; Budi Usodo (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research aims to know the different effect among learning used Group Investigation with Quantum Learning approach (GI-QL), Group Investigation (GI), and direct learning models. This research was quasi experimental research with factorial design of 3x3x2. The population of this research was the seventh grade students of State Junior High School of District Pringsewu in The Academic Year 2013/2014. The sampling technique used was stratified cluster random sampling. The data analysis used a three way analysis of variance with different cell at significance levels 0.05. The results of this research was as follows: (1) learning used GI-QL results better learning achievement than GI and direct learning models do, and GI results better learning achievement than direct learning models does, (2.a) at learning used GI-QL, kinesthetic, auditory, and visual learners have the same learning achievement; at learning used GI, visual learners have better learning achievement than auditory, and kinesthetic and auditory learners have the same learning achievement; whereas at learning used direct learning models, kinesthetic learners have better learning achievement than visual and kinesthetic learners, and visual and kinesthetic learners have the same learning achievement, (2.b) for kinesthetic and auditory learners, GI-QL results better learning achievement than GI and direct learning models do, and GI and direct learning models result the same learning achievement; and for visual learners, GI-QL and GI result the same learning achievement but better than direct learning models, and GI results better learning achievement than direct learning models does, (3.a) at each of learning models, students with high learning creativity have better learning achievement than low learning creativity, (3.b) at each of learning creativity categories, GI-QL results better learning achievement than GI and direct learning models do, and GI results better learning achievement than direct learning models does, (4.a) at each of learning models with each of learning styles, students with high learning creativity have better learning achievement than low learning creativity, (4.b) at each of learning models with each of learning creativity, visual learners have the same learning achievement with kinesthetic learners but it better than auditory learners, and auditory learners have better learning achievement than kinesthetic learners, (4.c) at each of learning styles with each of learning creativity, GI-QL results better learning achievement than GI and direct learning models, and GI results better learning achievement than direct learning models.Keywords: Group Investigation, Quantum Learning, Direct Learning, Learning Style, Learning Creativity.